Acute purulent exacerbation of chronic obstructive pulmonary disease and Chlamydia pneumoniae infection - KARAKURT, SAİT; KORTEN, VOLKAN (AMER THORACIC SOC, 1999)
In order to investigate the role of bacteria, including Mycoplasma pneumoniae and especially Chlamydia pneumoniae in acute purulent exacerbations of chronic obstructive pulmonary disease (COPD), we examined sputum specimens and acute and convalescent sera taken 26 d apart from 49 outpatients experiencing an acute purulent exacerbation of COPD. The sera were tested for antibodies to C, pneumoniae with the microimmunofluorescence test, and for antibodies to M. pneumoniae with the indirect fluorescence antibody test. Routine microbiologic culture of sputum yielded potentially pathogenic microorganisms in 12 of the 49 patients (24%). Three patients (6%) showed serologic evidence of recent M. pneumoniae infection. Seven patients showed high IgG titers of greater than or equal to 1:1,024 to C. pneumoniae, and an additional four had a fourfold increase in IgG titer, suggesting reinfection with C. pneumoniae. Sputum from two of these 11 patients also grew Streptococcus pneumoniae, and one grew Moraxello cotarrhalis. Patients with and without serologic evidence of current C. pneumoniae infection showed no significant differences in clinical features or pulmonary function. The high incidence of infection with C, pneumoniae (the sole causal agent in 16% of cases, and the causal agent with other agents in 6%) provides insight into the importance of this organism among agents leading to exacerbations of COPD in Turkey.
Keywords: BRONCHITIS; ANTIBODIES; TWAR; COPD